IN THE LIMITS OF GIVENNESS AND POSSIBILITY. EARLY LINGUISTIC WORKS OF LUBOMÍR DOLEŽEL IN CONTEXT - Fořt, Bohumil (Bohemica Olomucensia, 2022)
The study focuses on the linguistic work of Lubomír Doležel, a Czech - Canadian philologists and theoretician. This part of the author's oeuvre can be demarcated historically by the 1950s and 1960s and also methodologically by Marxist linguistics, structuralist linguistics and literary theory, and mathematical linguistics. The study declares and analyses the development of the author's approach to linguistic inquiry - starting from his general linguistic thought and moving towards the application of structuralist and mathematical methods for the purpose of the analysis of style, which ultimately led the author to the articulation of essential methodological axioms of his further literary theoretical work.
Keywords: Lubomír Doležel; linguistics; structuralism; literary theory; Marxism